Optical and electrical properties of thiarubrine A simulated via the Hückel method and the nonequilibrium Green’s function - Scotognella, Francesco (Frontiers in Photonics, 2025)
IntroductionThiarubrine A, a fascinating class of linear carbon chains, can be extracted from certain plants and are known for their photolabile pigment properties.MethodsIn this study, a modified Hückel method to investigate the optical properties of thiarubrine A has been employed, determining its absorption spectrum and wavelength-dependent complex refractive index. Additionally, using the nonequilibrium Green’s function formalism, the conductance of a single thiarubrine A molecule has been derived.Results and discussionLight absorption, complex refractive index dispersion, and conductance of thiarubrine A have been simulated. Exploiting its photolability, a light-induced switch in single-molecule conductance has been demonstrated through ultraviolet-visible irradiation, which produces a photoproduct containing a thiophene group. These findings enhance our understanding of the optical properties of naturally occurring polyynes and highlight their potential applications in single-molecule junctions for nanoelectronics.